Business economics : BBA-3rd semester - Lekhi, R.K (Kalyani Publishers, 2016)
Business economics : BBA-3rd semester / Lekhi, R.K. -- kolkata: Kalyani Publishers, 2016 338.5 L536e2 2nd rev. ed. No. of Copies : 1